Ionic liquid - Electrode materials interactions studied by NMR spectroscopy, cyclic voltammetry, and impedance spectroscopy - Zhang, E.; Fulik, N.; Paasch, S.; Borchardt, L.; Kaskel, Stefan; Brunner, Eike (Energy Storage Materials, 2019)
The interactions between two selected porous carbon materials and ionic-liquid based electrolyte solutions consisting of the ionic liquid 1-Ethyl-3-methylimidazolium tetrafluoroborate (EmimBF4)diluted with acetonitrile are investigated within the present paper by combined use of cyclic voltammetry, electrochemical impedance spectroscopy, and NMR spectroscopy. The commercially available microporous YP50F and the hierarchically organized micro- and mesoporous OM-CDC (ordered mesoporous carbide derived carbon)are selected as model materials to achieve a better understanding of the electrolyte behavior, especially its mobility, in porous carbons. The ionic liquid chosen as electrolyte leads to high specific capacitance approaching 180 F g-1 for OM-CDC. Due to the hierarchical pore system, OM-CDC shows a better rate performance than YP50F. NMR analyses provide an understanding of the molecular processes giving rise to the above-mentioned observations. They reveal a limited accessibility of the narrow pores in YP50F for pure EmimBF4 in contrast to OM-CDC. It was found that about 30% of the entire pore volume of YP50F remain unfilled by electrolyte ions without dilution. Dilution with acetonitrile significantly increased the anion mobility as the NMR signal of adsorbed ions becomes narrower. A mixture containing 60% EmimBF4 and 40% acetonitrile was identified as the optimum for electrochemical applications.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Ionic liquid; NMR spectroscopy; Porous carbon material; Supercapacitor